The Al-Qur’an Learning Evaluation Concept - Rofiudin, M. Rizal; Ishaq, Ishaq; Mukaffan, Mukaffan (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study is to describe the evaluation of learning from the perspective of the Qur'an. This research is qualitative with a library research approach. Data collection techniques are done with documentation. Then, analyze the data with data reduction, presentation, conclusion drawing, and verification. Based on the description and research results above in Islamic education, several basic terms are always connoted with the term evaluation, such as al-Qadha, al-Bala', al-Hisab, al-Imtihan, and al-Fitnah. Although these terms have different orientations of meaning, all five have similar functions in education. The primary evaluation process measures the achievement of learning or educational programs in schools and outside schools. Learning evaluation serves to identify the achievement of learning objectives and provide information on what should be done to overcome the weaknesses obtained in the activities that have been carried out.